Método Polya para mejorar la competencia resuelve problemas de cantidad del área de matemática en estudiantes de quinto grado de primaria de la institución educativa N° 60025 Padre Severino Deshaies, río Amazonas 2024 - Vilchez Alegria, Vanessa Yusita (2025)
The main objective of the study was to evaluate if Pólya's method improves the competence to solve quantity problems in fifth grade students of I.E. N° 60025 Padre Severino Deshaies, Río Amazonas 2024. The design was quasi- experimental, considering an experimental and control group with 29 and 30 students respectively. A pretest and a posttest were applied to measure competence before and after implementing the Pólya method in the experimental group. To evaluate the dependent variable, a questionnaire with 20 questions was used, previously validated by experts and applied in both groups. The population consisted of 59 fifth grade schoolchildren. The results of the statistical analysis using Student's t-test showed a significant improvement in the experimental group (posttest mean=70.07, tc=4.479, p< 0.000). It was concluded that the implementation of Pólya's method proved to be an effective tool to strengthen the competence to solve quantity problems in fifth grade students. Strengthening skills such as interpretation, communication, calculation and mathematical argumentation.